STRATEGI DIGITAL MARKETING DALAM PENINGKATAN NASABAH DI BANK MUAMALAT SAAT PANDEMI COVID-19 (Studi Kasus Bank Muamalat Kota Malang Saat Pandemi Covid-19) - Elia Nurmala; Maslichah Maslichah; M Cholid Mawardi (Universitas Islam Malang, 2022)
Marketing is an activity that must be carried out by every activity economics, especially in each financial institution. Because by being these marketing activities, the purpose of a company or organization. and institutions can be achieved. And it is undeniable that changes will The inevitable globalization of technology demands that every company, institutions and organizations to be more sensitive so as to encourage creativity and innovation of a person in the marketing process so as not to be left behind by the times. Digital marketing is the main priority in this research to what extent is the target is able to apply the digitization. The main purpose of the research this is to analyze digital marketing applied to the Bank Muamalat Malang City Branch Office as a strategy in increasing customers in some period of time, which from the past the institution has using a traditional marketing system which then switches to a digitization. From the system transition, it was found that there was unrest ordiscrepancy due to several factors. This study uses qualitative research by conducting interviews, and documentation. The results of this study say that The digital marketing used is felt to be not optimal due to the obstacles faced. In addition, the process of switching the system becomes a challenge especially in the current pandemic era. As for the things faced in Bank Muamalat Malang City influenced by internal factors, namely, HR background, inadequate facilities, and less than optimal software as well as external factors, namely the colonial community and the poor technology literate. Therefore, there is a need for follow-up on the problem These are in the form of HR training, improvement of facilities, and development better software and there must be an approach to the community by providing an understanding of the importance of technology and also providing the best service so as to increase customer confidence.